Enhanced cometabolism of benzo(a)anthracene by the lignin monomer vanillate is related to structural and functional responses of the soil microbiome. (October 2020) - Sun, Yue; Liu, Linmeng; Zeng, Jun; Wu, Yucheng; Lin, Xiangui
Abstract: Lignin is a natural polymer composed of phenolic units. The structural similarity between lignin monomers and recalcitrant aromatic pollutants raises the possibility of their cometabolism by soil microorganisms. Here, we explored the links between polycyclic aromatic hydrocarbon (PAH) degradation and microbiome responses in soil microcosms amended with lignin or one of its phenolic units, vanillate, by coupled amplicon and metagenomic shotgun sequencing. The transformation of the four-ring model PAH benzo(a)anthracene (BaA) was monitored by using a radiolabelled tracer. The results demonstrated that vanillate significantly promoted 14 CO2 production during incubation, suggesting activation of BaA biodegradation in the soil microcosms. Lignin changed the fate of BaA mainly by increasing its adsorption to soil organic matter. In contrast to the control microcosms, the mineralization and formation of nonextractable residue (NER) from BaA in the presence of vanillate were sensitive to the fungicide cycloheximide. Lignin and vanillate consistently enriched bacterial methyl utilization and aromatic ring cleavage genes at the two sampling times, which, however, did not result in BaA mineralization. The distinct responses of the fungal community to vanillate as well as the coupled cycloheximide-induced inhibition of BaA mineralization and 18S rRNA gene abundance suggest an essential contribution of fungi to BaA biodegradation in the vanillate-amended microcosms. Overall, these findings reveal a cometabolic mechanism between vanillate and PAHs, which contributed to the detoxification of BaA in the soil. This study also provides a scientific basis for the bioremediation of PAH-contaminated soil by priming the soil microbiome with phenolic monomers of lignin. Highlights: Mineralization of BaA in an arable soil was enhanced by vanillate. Sensitivity of BaA transformation to a fungicide varied across treatments. Upregulation of bacterial MAC genes did not translate to BaA mineralization. Fungal contribution to BaA cometabolism in vanillate treatment increased.